2023
DOI: 10.3389/fnut.2023.1046686
|View full text |Cite
|
Sign up to set email alerts
|

Sociodemographic inequalities in vegetables, fruits, and animal source foods consumption in children aged 6–23 months from 91 LMIC

Abstract: IntroductionNo multi-country analysis described patterns and inequalities for the brand-new feeding indicators proposed by WHO/UNICEF: zero consumption of vegetables and fruits (ZVF) and consumption of eggs and/or flesh (EFF). Our aim was to describe patterns in the prevalence and social inequalities of ZVF and EFF among children aged 6–23 months in low-and middle-income countries.MethodsData from nationally representative surveys (2010–2019) in 91 low-and middle-income countries were used to investigate withi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
2
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 20 publications
4
2
0
1
Order By: Relevance
“…By 24 months of age, the average consumption of ASF ranged from 20% to 34% for all sites combined. Our findings matched previous research reporting that consumption of ASF, especially flesh foods and eggs, were low globally for children of complementary feeding age (Krebs et al, 2011 ; Ricardo et al, 2023 ). When we combined the ASF groups (meat, fish, insects; eggs; milk and dairy) and examined the relationship with LAZ, we observed a positive association at 24 months (Table 2 ).…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…By 24 months of age, the average consumption of ASF ranged from 20% to 34% for all sites combined. Our findings matched previous research reporting that consumption of ASF, especially flesh foods and eggs, were low globally for children of complementary feeding age (Krebs et al, 2011 ; Ricardo et al, 2023 ). When we combined the ASF groups (meat, fish, insects; eggs; milk and dairy) and examined the relationship with LAZ, we observed a positive association at 24 months (Table 2 ).…”
Section: Discussionsupporting
confidence: 92%
“…By 24 months, the consumption was over 90%, consistent with the community's heavy reliance on cassava leaves and other dark leafy greens and recipes with red palm oil, all of which contribute to vitamin‐A intake (Lander et al, 2019 ). The findings that India had the greatest increase in the number of food groups eaten from 6 to 24 months but flesh foods and eggs remained below 50%, and that Guatemala had the highest intakes of flesh foods and eggs by 24 months of age support previous national survey findings (Ricardo et al, 2023 ).…”
Section: Discussionsupporting
confidence: 84%
“…More recently a multi-country study on vegetable and fruit consumption among children 6–23 months reported an overall prevalence of zero fruit or vegetable consumption in low-income and lower-middle-income countries of 45%. The study found that vegetable and fruit consumption was higher in wealthier countries and that overall poorer and rural children consumed less fruits and vegetables than their counterparts [ 18 ].…”
Section: Introductionmentioning
confidence: 99%
“…In contexts of socio-economic inequalities, the use of these indicators could be crucial, considering the immense threat that these extreme conditions may represent to ideal feeding practices (18)(19)(20)(21)(22) . This inability to provide adequate nutrition to small children (6-23•9 months) has a direct impact on their micronutrient status and growth (15) .…”
mentioning
confidence: 99%